CONCEPTUAL ANALYSIS OF ASSOCIATIVE UNITS IN THE UZBEKI LANGUAGE (World Bulletin of Social Sciences, 2023)
In the Uzbek language, the concept of the homeland is distinguished by its national-cultural character, its active use, and its realization through lexical, paremiological, and syntactic expressive units. The concept of the homeland is the basis of religious, educational, spiritual, socio-political concepts.